Determinants of Entry and Exit in the Malaysian Manufacturing Sector - Abdullah, Ahmad Zainuddin (2005)
This study highlights the determinants of entry and exit of fums in the Malaysian manufacturing sectors. The findings from this study will assist policy makers in formulating effective competition policy and draw more interests for future research in this area. Entry and exit are crucial determinants of market structure and performance. The existence of barriers to entry will impede the process of creating more competitive market structure and hence, lead to inefficient resource allocation. In the process, entry and exit of firms are directly measured. Determinants of entry and exit are then grouped based on incentives and impediments to entry and exit. Initially the determinants of entry and exit separately considered. Next, symmetric relationship between the two was examined since barriers to entry can also be barriers to exit. Finally, simultaneous relationship between entry and exit whereby entry forces exit and exit attracts entry was also examined. The evidence on entry and exit of firms shows that entry and exit in the Malaysian manufacturing sectors are very intense, however they occur at the bottom of the industry structure.